A comprehensive study on the impacts of rock fabric on hydrocarbon generation and pore structure evolution of shale under semi-confined condition. (February 2021) - Song, Dongjun; Wang, Xiaoqi; Tuo, Jincai; Wu, Chenjun; Zhang, Mingfeng; Su, Long; He, Wei
Abstract: Semi-confined pyrolysis experiments were performed on core and powdered samples taken from type-II lacustrine mudstone to investigate the effects of sample rock fabrics on hydrocarbon generation and porosity changes when shale is subjected to pyrolysis. The generated hydrocarbons were analysed by organic geochemical methods to reflect differences in constituents and carbon isotopes. Gas (N2 and CO2 ) adsorption tests were applied to solid residues to characterize the formation and development of pores after the two series of pyrolysis experiments. Simple calculations indicate that hydrocarbons prefer to expulse as intact rock fabric is destroyed. Secondary cracking gas accounted for approximately 23–30% and 28–49% of all gaseous hydrocarbons in the powdered and core samples, respectively. Side reactions, such as mineral catalytic and recombination reactions, prevailed during the semi-closed pyrolysis of powdered sample at 300–500 °C, causing generated C3+ hydrocarbon yields to be lower than those of the core sample. Additionally, gaseous hydrocarbons generated from the powdered sample were characterized by more positive δ 13 C and higher iso -/ n -C4, 5 and C1 /C1-5 values. Side reactions ceased at 500–550 °C, and corresponding ratios tended to equalize. For the powdered samples, a higher expulsive ratio of hydrocarbons led to better pore development, the mesopore volume increased with increasing temperatures, and micropore volume decreased above 450 °C. Comparatively, the mesopore volume decreased above 450 °C for the core sample, and the micropore volume decreased above 500 °C. These results are helpful for revealing the genetic characteristics of shale gas and for understanding the origins of organic-hosted pores of the Cambrian Niutitang shale in southern China. The study suggests that samples with intact rock fabric should be used in future laboratory pyrolysis tests to generate results that better reflect natural conditions. Highlights: Semi-closed pyrolysis results for core and powdered samples of a same mudstone were compared. The expulsion-retention mechanisms of hydrocarbons are affected by rock fabrics. Rock fabrics have important effects on porosity development of samples. Samples with intact rock fabrics should be used for future laboratory pyrolysis.